Prevalence and Serotype Diversity of Salmonella in Apparently Healthy Cattle: Systematic Review and Meta-Analysis of Published Studies, 2000–2017 - Gutema, Fanta D.; Agga, Getahun E.; Abdi, Reta D.; De Zutter, Lieven; Duchateau, Luc; Gabriël, Sarah (Frontiers in Veterinary Science, 2019)
Salmonellosisis a leading cause of foodborne illnesses in humans with cattle being one of the reservoirs for Salmonella. We estimated a pooled prevalence of Salmonella apparently healthy Cattle and examined serotype diversity through systematic review and meta-analysis of studies published between 2000-2017. Peer reviewed publications reporting the prevalence of Salmonella in cattle were searched through five electronic databases (PubMed, Google scholar, Agricola, Scopus, CAB direct) and through manual search. We obtained 71 publications with 75 datasets consisting of a total of 52,766 animals examined and 5,010 Salmonella positive cattle from 29 countries in six continents (except from Antarctica). Pooled prevalence of Salmonella in cattle was 9% (95% confidence interval: 7-11%).Significantly high heterogeneity (I2=98.7%, P < 0.01) was observed among all studies as well as within continents. Prevalence varied from 2% (Europe) to 16% (North America).Overall, 143different serotypes were reported with the most diverse serotypes being reported from Africa (76different serotypes) followed by North America (49 serotypes). The ten most frequently reported serotypes (Montevideo, Typhimurium, Kentucky, Meleagridis, Anatum, Cerro, Mbandaka, Muenster, Newport and Senftenberg) accounted for 65% of the isolates for which specific serotype information was reported. Salmonella Montevideo and S. Dublin are the most frequently reported serotypes in North America and Europe, respectively, while S. Typhimurium was the most frequent in Africa, Asia and Australasia. Our results indicate variability both in the prevalence and serotype diversity of Salmonella in cattle across continents. Although all Salmonella serotypes are potentially pathogenic to humans, five (Montevideo, Typhimurium,Anatum, Mbandaka, and Newport) of the top 10 serotypes identified in this study are among the serotypes most commonly associated with clinical illnesses in humans.